2015
DOI: 10.1007/s00404-015-3900-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of citalopram and venlafaxine’s role in treating sleep disturbances in menopausal women, a randomized, double-blind, placebo-controlled trial

Abstract: Iranian Registry of Clinical Trials 201210152576N6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…CBTi has been shown to be effective in insomnia in this group, with long lasting benefits up to six months post-treatment (McCurry et al, 2016). There are modest benefits from some but not all studies of pharmacotherapy with SRIs including escitalopram, citalopram and venlafaxine although short duration of follow-up limits the conclusions that can be drawn from the studies (Ensrud et al, 2012; Davari-Tahna et al, 2016).…”
Section: Special Populationsmentioning
confidence: 99%
“…CBTi has been shown to be effective in insomnia in this group, with long lasting benefits up to six months post-treatment (McCurry et al, 2016). There are modest benefits from some but not all studies of pharmacotherapy with SRIs including escitalopram, citalopram and venlafaxine although short duration of follow-up limits the conclusions that can be drawn from the studies (Ensrud et al, 2012; Davari-Tahna et al, 2016).…”
Section: Special Populationsmentioning
confidence: 99%
“…SNRIs may have a consistent antidepressant effect in women across different ages and menopausal staging. In their study on sleep-related issues, Davari-Tanha et al suggested that venlafaxine is more efficacious than citalopram in the treatment of depression in postmenopausal women [ 21 ]. The results from the present study confirm and extend these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Эффект развивался достаточно быстро, в течение двух недель. Нормализация сна, улучшение настроения и снижение тревожности также приветствуются, т. к. в целом повышают качество жизни [9,11,30].…”
Section: ингибиторы обратного захвата серотонинаunclassified